International survey of diagnostic services for children with Fetal Alcohol Spectrum Disorders - Bower Carol; Fremantle Emily; Peadon Elizabeth; Elliott Elizabeth J (BMC, 2008)
Abstract Background Early diagnosis and intervention for children with Fetal Alcohol Spectrum Disorder (FASD) reduces the risk of developing a range of secondary social, emotional and behavioural problems and provides an opportunity for prevention of further alcohol exposed pregnancies. The objective of this study was to describe specialist clinical service provision for the diagnosis and assessment of children exposed to alcohol in pregnancy. Methods Fetal Alcohol Spectrum Disorder (FASD) diagnostic clinics were identified through literature and internet searches. Clinics were sent a questionnaire asking for information on the clinic population, clinic staff, assessment process and other services provided. Results Questionnaires were completed for 34 clinics: 29 were in North America, 2 in Africa, 2 in Europe and 1 in South America. No clinics were identified in Asia or Australasia. There was a variety of funding sources, services offered, clinic populations, staff and methods of assessment. Thirty-three clinics had a multi-disciplinary team. In 32 clinics, at least one member of the team had specialist training in assessment of FASD. Neurobehavioural assessment was completed in 32 clinics. Eleven clinics used more than one set of diagnostic criteria or an adaptation of published criteria. Conclusion Diagnostic services are concentrated in North America. Most responding clinics are using a multidisciplinary approach with neurobehavioural assessment as recommended in published guidelines. Agreement on diagnostic criteria would enable comparison of clinical and research data, and enhance FASD research particularly for intervention trials.